2012
DOI: 10.1289/ehp.1104179
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent Chromium Cr(VI) Up-Regulates COX-2 Expression through an NFκB/c-Jun/AP-1–Dependent Pathway

Abstract: Background: Hexavalent chromium [Cr(VI)] is recognized as a human carcinogen via inhalation. However, the molecular mechanisms by which Cr(VI) causes cancers are not well understood.Objectives: We evaluated cyclooxygenase-2 (COX-2) expression and the signaling pathway leading to this induction due to Cr(VI) exposure in cultured cells.Methods: We used the luciferase reporter assay and Western blotting to determine COX-2 induction by Cr(VI). We used dominant negative mutant, genetic knockout, gene knockdown, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Previous studies have shown that AP-1, HIF-1α, Cox-2, and iNOS play an important role in carcinogenesis (Gao et al , 2002; Li et al , 2006; Farinati et al , 2010; Zuo et al , 2012). We investigated the effect of luteolin on Cr(VI)-induced transactivation of AP-1, HIF-1α, Cox-2, and iNOS using a luciferase reporter assay in BEAS-2B cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that AP-1, HIF-1α, Cox-2, and iNOS play an important role in carcinogenesis (Gao et al , 2002; Li et al , 2006; Farinati et al , 2010; Zuo et al , 2012). We investigated the effect of luteolin on Cr(VI)-induced transactivation of AP-1, HIF-1α, Cox-2, and iNOS using a luciferase reporter assay in BEAS-2B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is a key enzyme in the conversion of arachidonic acid to prostanoids, and its activation is associated with inflammation and carcinogenesis (Hakozaki et al , 2014). Elevated COX-2 expression has been demonstrated in Cr(VI)-exposed cultured cells (Zuo et al , 2012; Son et al , 2013). Pro-inflammatory cytokines, including interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor-alpha (TNF-α) are involved in several pathological processes (Bouraoui et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other systems, ROS are recognized as activators of AP-1; however, the signaling transduction events involved are not totally understood. Chromium, cobalt, cadmium and vanadium are metals involved in the activation of AP-1 through signaling cascades involving the production of ROS and comprised of proteins and enzymes such as thioredoxin (Trx), redox factor-1 (Ref-1), ERK/MAPK, NADPH oxidase, I kappa B kinase (IKK), p38, JNK/c-jun [117,131,132].…”
Section: Some Ros Such As Omentioning
confidence: 99%
“…For example, based on a review of relevant data (e.g., genetic characterization of CrVI-induced tumors, in vivo and in vitro genotoxicity/mutagenicity test results, epigenetic changes), Holmes et al (2008) proposed a mechanism for CrVI-induced lung carcinogenesis that involves genomic instability due to DNA double strand break-induced G2 arrest (as opposed to mutation in multistage carcinogenesis) ultimately resulting in neoplastic transformation and cancer. Other MOAs and mechanisms for CrVI-induced carcinogenicity have also been proposed (e.g., Zuo et al, 2012;Xie et al, 2008;Thompson et al, 2011), such as mutagenicity as the initiating step (McCarroll et al, 2009;USEPA, 2010) or cellular resistance to CrVI-induced death through dysregulated DNA repair and/or survival signaling and transcriptional repatterning (Nickens et al, 2010). As the earliest key events, what the proposed MOAs have in common is an assumption (inherent or explicitly stated) that CrVI has escaped extracellular reduction to enter cells of the target tissue, followed by the intracellular reduction of CrVI.…”
Section: Carcinogenic Moamentioning
confidence: 99%